Overlapping and Continued Alendronate or Raloxifene Administration in Patients on Teriparatide: Effects on Areal and Volumetric Bone Mineral Density—The CONFORS Study. (August 2014) - Muschitz, Christian; Kocijan, Roland; Fahrleitner‐Pammer, Astrid; Pavo, Imre; Haschka, Judith; Schima, Wolfgang; Kapiotis, Stylianos; Resch, Heinrich
Abstract Nine month teriparatide (TPTD) monotherapy followed by co‐administration of raloxifene (RAL) or alendronate (ALN) for another nine 9 months resulted in incremental bone mineral density (BMD) increase. The aim of this study was to investigate the effects of continued antiresorptive treatments for 12 months in the extension phase. Postmenopausal women (n = 125) with severe osteoporosis on ongoing TPTD treatment for 9 months were randomized into three open‐label groups for another 9 months: ALN (70 mg/week, n = 41), RAL (60 mg/d, n = 37) in addition to TPTD or no additional medication (n = 47) except Ca and vitamin D. After discontinuation of TPTD the respective antiresorptives were continued for a further 12 months, while patients in the TPTD monotherapy group received Ca and vitamin D. Amino‐terminal propeptide of type I procollagen (P1NP) and cross‐linked C‐telopeptide (CTX), areal and volumetric BMD at the lumbar spine (LS) and hip were assessed. ALN resulted in continued BMD increase in LS (4.3 ± 1.5%; mean ± SD), femoral neck (4.2 ± 1.6%) and total hip (4 ± 1.6%; p < 0.001 for all), while RAL was only effective at the LS (2.4 ± 1.7%, p < 0.001) but no changes at the femoral neck (0.4 ± 1.4%) or total hip (−0.8 ± 1.5%) were observed. Cortical bone only increased in the ALN group (femoral neck 6.7 ± 2.7% and −1.3 ± 2.5%; total hip 13.8 ± 2.9% and −2.3 ± 2.5% for ALN and RAL, p < 0.001 for all; respectively). Analyzing the entire 30 months of therapy, the ALN group revealed the largest BMD increase in all regions. Our results suggest that the addition of ALN to ongoing TPTD and continuing ALN after TPTD was stopped may be beneficial for patients in terms of areal and volumetric BMD increase. Further research is warranted to determine the optimal timing of the initiation of the combination treatment, the respective antiresorptive medication and the potential benefit of this BMD increase regarding fracture prevention. © 2014 American Society for Bone and Mineral Research